2022
DOI: 10.1007/s12598-022-01981-8
|View full text |Cite
|
Sign up to set email alerts
|

Single-bit full adder and logic gate based on synthetic antiferromagnetic bilayer skyrmions

Abstract: Skyrmion-based devices are promising candidates for non-volatile memory and low-delay time computation. Many skyrmion-based devices execute operation by controlling skyrmion trajectory, which can be impeded by the skyrmion Hall effect. Here, the design of skyrmionbased arithmetic device built on synthetic antiferromagnetic (SyAF) structures are presented, where the structure can greatly suppress skyrmion Hall effect. In this study, the operations of skyrmion-based half adder, full adder and XOR logic gate are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…[60] Here, we simulate the SAF skyrmion logic functions using the Object Oriented Micromagnetic Framework (OOMMF) with an extended module of the Dzyaloshinskii-Moriya interaction. [61] For micromagnetic simulations, the standard magnetic material parameters of Co/Pt multilayers are used for the SAF structure: [27,29,42,45,59]…”
Section: Model and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[60] Here, we simulate the SAF skyrmion logic functions using the Object Oriented Micromagnetic Framework (OOMMF) with an extended module of the Dzyaloshinskii-Moriya interaction. [61] For micromagnetic simulations, the standard magnetic material parameters of Co/Pt multilayers are used for the SAF structure: [27,29,42,45,59]…”
Section: Model and Methodsmentioning
confidence: 99%
“…In particular, a logic switching delay is determined by the skyrmion velocity and the distance between the input and output terminals. [45,49] Therefore, the trade-off between skyrmion-based logic gates' response speed and energy consumption needs to be considered. [48] Namely, a smaller driving current can decrease the energy consumption and a large current can be adopted for high switching speed.…”
Section: Realization Of Not Logic Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…30,31 SkHE was shown to be suppressed by employing synthetic anti-ferromagnets. 32 However, the skyrmion stability issue persists with current-driven devices.…”
Section: Introductionmentioning
confidence: 99%
“…This area of research has shown great potential since the discovery of Giant Magnetoresistance by Albert Fert and Peter Grunberg, for which they were awarded the Nobel Prize in 2007 [2,3]. Spintronics has served as the foundation for various devices such as magnetic random-access memories (MRAMs) [4,5], logic gates [6][7][8][9], racetrack memories [10,11], sensors [12,13], and artificial neuron synapses [8,[14][15][16]. Despite the technological advancements, spintroncis is still a topic of investigation in terms of the challenges related to energy costs and data capacity [17,18].…”
Section: Description Unitmentioning
confidence: 99%